2019
DOI: 10.1371/journal.pone.0210478
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy assessment of commercially available natural products and antibiotics, commonly used for mitigation of pathogenic Vibrio outbreaks in Ecuadorian Penaeus (Litopenaeus) vannamei hatcheries

Abstract: Bacterial diseases cause high mortality in Penaeus (Litopenaeus) vannamei postlarvae. Therefore, appropriate application of efficient therapeutic products is of vital importance for disease control. This study evaluated through in vitro analyses the antimicrobial effectiveness of commercial therapeutic products used for P. vannamei bacterial diseases and antibiotics against pathogenic Vibrio strains circulating in Ecuadorian hatcheries. Twenty strains were isolated from 31 larvae samples with high bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…In addition, well-documented toxic effects of florfenicol on fish and crustacean larvae [69][70][71][72] indicate the urgent need for considering the use of alternative strategies to control pathogenic bacteria in live feeds administered to marine fish aquaculture, including bacteriophages, probiotics, and natural products [42,73,74]. In a recent study, probiotics, organic acids, and essential oils were demonstrated to be effective at controlling the pathogenic activity of vibrios on A. franciscana nauplii [75]. Thus, using live feeds as carriers for non-antibiotic therapeutic applications in marine fish cultures appears to be a very attractive option.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, well-documented toxic effects of florfenicol on fish and crustacean larvae [69][70][71][72] indicate the urgent need for considering the use of alternative strategies to control pathogenic bacteria in live feeds administered to marine fish aquaculture, including bacteriophages, probiotics, and natural products [42,73,74]. In a recent study, probiotics, organic acids, and essential oils were demonstrated to be effective at controlling the pathogenic activity of vibrios on A. franciscana nauplii [75]. Thus, using live feeds as carriers for non-antibiotic therapeutic applications in marine fish cultures appears to be a very attractive option.…”
Section: Discussionmentioning
confidence: 99%
“…They can also reduce the ability of bacterial pathogens to adhere to epithelial cells in vitro (e.g., Daphnetin, a coumarin-derivative) by reducing the expression of H. pylori genes involved in colonisation [30]. Antimicrobial mixtures of probiotics, organic acids and essential oils were effective in reducing the devastating impact of Vibrio strain infections in South American farmed shrimps [31]; however, the study did not elucidate the biological mechanism responsible for the effect.…”
Section: Discussionmentioning
confidence: 94%
“…Antibiotics and probiotics are some of the common treatment methods for most strains of pathogenic bacteria found in aquaculture systems (Yu et al 2012;Miranda et al 2013;Sotomayor et al 2019). However, the use of antibiotics often resulted in the development of multidrugresistant strains, raising concerns about consumer's health and economic threat (Miranda et al 2013;Lee et al 2018) whereas probiotics are species-specific, involve precise dosage administration, and research on probiotic as biocontrol is still limited (Hosseinifar et al, 2018).…”
Section: Bacteriamentioning
confidence: 99%
“…2013; Sotomayor et al . 2019). However, the use of antibiotics often resulted in the development of multidrug‐resistant strains, raising concerns about consumer’s health and economic threat (Miranda et al .…”
Section: Disease In Aquaculturementioning
confidence: 99%